2013
DOI: 10.1177/155892501300800304
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Elements and Abrasion Resistance Tests for Car Seat Upholstery

Abstract: The weight of textile components in automobiles is expected to rise to 35 kg by 2020, and the average lifetime of a vehicle is about 12 years. Car seats are the most important part of the interior decoration, and polyester is the most widely used material in car seat covering. Abrasion resistance tests are used to quantify the duration of car seat upholstery in normal usage, and this is one of the most important requirements. Several testing methods, standards, and car producer specifications have been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…It was found that cars with ramie blended seat covers were more comfortable based on the subjective evaluation collected from a questionnaire of five questions and these results were consistent with the objective measurements [15]. Jerkovic et.al examined Martindale, Schopper, and Transverse abrasion resistance testers and the methods were compared with each other using P320, P400, P600 abrasive papers [16]. Mecit et.al investigated automotive industry applications for recyclable products.…”
Section: Introductionmentioning
confidence: 68%
“…It was found that cars with ramie blended seat covers were more comfortable based on the subjective evaluation collected from a questionnaire of five questions and these results were consistent with the objective measurements [15]. Jerkovic et.al examined Martindale, Schopper, and Transverse abrasion resistance testers and the methods were compared with each other using P320, P400, P600 abrasive papers [16]. Mecit et.al investigated automotive industry applications for recyclable products.…”
Section: Introductionmentioning
confidence: 68%
“…Automotive textiles have a large share in the global technical textiles market, which is comprised of seat upholstery, floor covering, headliners, door coverings, pillar coverings, safety belts, side panel coverings, airbags, tires, sound, and thermal insulators [1,2]. Automotive interior textiles are usually made of woven, warp knitted, weft knitted, laminated and nonwoven fabrics [3,4]. The seat upholsteries are of great importance, due to their effect on the driver and passenger comfort, and also the aesthetic appeal of the interior scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the effect of fabric and lamination-foam properties on the air permeability of laminated headrest fabrics. Tekstil ve Konfeksiyon, 31 (4), 235-241. Car seat upholstery is generally made of different structures. The one layer of seat upholstery is the lamination foam, mostly made of PU due to the comfort and protection level served by PUs which is not achieved by any other single structure [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, automakers are increasingly favoring the usage of weft-knitted fabrics for different interior components, such as seat covers, dashboard covers, side panels, etc. Some researchers have extended their studies to focus on improving the performance of fabrics used in the automotive industry, such as resistance to abrasion [ 10 , 11 , 12 ], tensile and tear properties [ 9 , 13 , 14 ], thermal stability [ 15 , 16 ], flame retardance [ 17 , 18 ] and physiological properties [ 19 ]. Researchers have also focused on other functional properties of automotive interior materials, such as sound absorption [ 20 , 21 , 22 , 23 ] and water and oil repellency [ 24 ].…”
Section: Introductionmentioning
confidence: 99%